2015
DOI: 10.1007/s00330-015-3727-y
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric CT dose: a multicentre audit of subspecialty practice in Australia and New Zealand

Abstract: • SSDEs can be calculated for all patients, CT systems, and practices • Kilovoltage peak (kVp) has the greatest association with dose in similar-sized patients • Paediatric DRRs for CT are now available for use internationally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
(35 reference statements)
0
11
0
Order By: Relevance
“…Table 4 shows the distribution of effective doses. A comparison of DRLs obtained from this study with published DRLs is shown in Table 5 [ 9 14 15 16 18 19 20 21 ]. In our study, for the body weight of 5, 15, 30, 50, and 80 kg, CTDI vol of DRLs were 1.4, 2.2, 2.7, 4.0, and 4.7 mGy, respectively, for abdominopelvic CT and 1.2, 1.5, 2.3, 3.7, and 5.8 mGy, respectively, for chest CT.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 4 shows the distribution of effective doses. A comparison of DRLs obtained from this study with published DRLs is shown in Table 5 [ 9 14 15 16 18 19 20 21 ]. In our study, for the body weight of 5, 15, 30, 50, and 80 kg, CTDI vol of DRLs were 1.4, 2.2, 2.7, 4.0, and 4.7 mGy, respectively, for abdominopelvic CT and 1.2, 1.5, 2.3, 3.7, and 5.8 mGy, respectively, for chest CT.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, all hospitals used CT protocols designed according to the patient's body weight, and none of the hospitals used the body size or X-ray attenuation characteristics. Few studies conducted dose surveys for pediatric CT examinations by grouping patients according to the body size [ 14 15 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are reports available from several countries on the radiation dose used for temporal bone CT in children. A multicenter study showed that the median CTDI vol for temporal bone CT in children aged 1–5 years was 34 mGy in Australia and New Zealand . The third quartile value for CTDI vol in children aged 1–5 years was reported to be 66 mGy in Belgium and 71 mGy in France .…”
Section: Discussionmentioning
confidence: 99%
“…A multicenter study showed that the median CTDI vol for temporal bone CT in children aged 1-5 years was 34 mGy in Australia and New Zealand. 11 The third quartile value for CTDI vol in children aged 1-5 years was reported to be 66 mGy in Belgium 12 and 71 mGy in France. 13 Recently, the mean CTDI vol and DLP for temporal bone CT in children aged 1-5 years at a tertiary children's hospital in Japan was reported to be 21 mGy and 151 mGyÁcm, respectively.…”
Section: P-valuementioning
confidence: 99%